2015
DOI: 10.5897/ajar2014.9171
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effect of farmers practices on the severity of groundnut rosette virus disease in Uganda

Abstract: Groundnut rosette virus disease is the most destructive disease of groundnut in Sub-Saharan Africa, Uganda inclusive. Over the past years, a wide range of management options for this disease have been developed and recommended for farmers in Uganda. Relevant efforts have also been made by researchers in disseminating improved technologies to farmers in several parts of the country. However, questions on the extent to which farmers are currently utilizing these technologies and their effectiveness in controllin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In Uganda, groundnut is the second most important food legume after common beans (Phaseolus vulgaris L.) (Okello et al 2014;Kabeere and Wulf, 2008). The crop is popular, especially in the eastern and northern regions of the country where it has become part of peoples' culture (Rooner and Giller, 2012;Mugisa et al 2015). It is grown throughout the country in diverse environments including both dryland and rain fed conditions (Rooner and Giller, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Uganda, groundnut is the second most important food legume after common beans (Phaseolus vulgaris L.) (Okello et al 2014;Kabeere and Wulf, 2008). The crop is popular, especially in the eastern and northern regions of the country where it has become part of peoples' culture (Rooner and Giller, 2012;Mugisa et al 2015). It is grown throughout the country in diverse environments including both dryland and rain fed conditions (Rooner and Giller, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Literature pertaining to differences in plant growth of landraces versus improved varieties is not well documented. However, results from studies by Kakeeto (2018) found that plant height of groundnut materials tested in Uganda Reaction of selected improved groundnut varieties and landraces to natural pest and disease infestations Another important selection criterion used by groundnut producers is the pests and disease reaction (Okello et al 2010, Mugisa et al 2015). The reaction of groundnut varieties to pests and diseases didn't signi cantly differ between landraces and improved varieties, even though incidence of pests and diseases was lower on improved varieties.…”
Section: Comparison Of Growth Parameters Of Selected Improved Varieties and Landracesmentioning
confidence: 99%
“…In conjunction with nutrient balances, examination of the relationships among household demographic/socioeconomic characteristics and management practices can elucidate the factors driving farmer decision-making and further contextualize and assess the sustainability of agroecosystems (Nkonya et al, 2005;Ebanyat et al, 2010a). Socioeconomic and demographic factors such as gender of the household head or crop planner (Nijuki et al, 2008;Tanellari et al, 2014;Mugisa et al, 2015), land tenure (Place and Otsuka, 2002;Kassie et al, 2015), ethnic group (Naughton-Treves, 1997Kirner, 2010), and field distance from the homestead (Tittonell et al, 2005(Tittonell et al, , 2013Zingore et al, 2007a) have been shown to drive farmer practices and affect farmer access to, use, and decisions regarding resources like residues (Barrett and Bevis, 2015).…”
Section: Introductionmentioning
confidence: 99%